2011
DOI: 10.1016/j.seizure.2010.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of refractory simple motor status epilepticus with lacosamide and levetiracetam

Abstract: Lacosamide has been reported to have been successfully used for non-convulsive status epilepticus after benzodiazepine failure, and convulsive status epilepticus after benzodiazepine and levetiracetam failure. We report a case of simple motor status epilepticus refractory to benzodiazepines and multiple anti-epileptic medications (AEDs) over 4 days. The addition of lacosamide in combination with existing levetiracetam aborted the continuous seizure with maintenance of seizure freedom through the most recent fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 5 publications
1
29
0
1
Order By: Relevance
“…However, they supported the observation that the outcome at discharge seemed to depend considerably on the age of the patient and not on the therapeutic approach [3]. Chen et al presented a case of a 57-year-old male with refractory SPSE, already under levetiracetam, who became seizure-free after the initiation of lacosamide at an initial dosage of 50 mg bid and then gradually increased to 200 mg bid [4].…”
Section: Discussionmentioning
confidence: 75%
“…However, they supported the observation that the outcome at discharge seemed to depend considerably on the age of the patient and not on the therapeutic approach [3]. Chen et al presented a case of a 57-year-old male with refractory SPSE, already under levetiracetam, who became seizure-free after the initiation of lacosamide at an initial dosage of 50 mg bid and then gradually increased to 200 mg bid [4].…”
Section: Discussionmentioning
confidence: 75%
“…Both LCS and its metabolites are excreted in urine. [3][4][5][6] Three received oral LCM, 4-6 and 1 was treated through a gastrocutaneous fistula. Cardiovascular events have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…1 Data are lacking regarding simple partial RSE outcomes. [3][4][5][6] We present 2 patients with simple partial RSE, treated with a single oral dose of LCM (300 mg). 1 Currently, no prospective clinical trial on lacosamide (LCM) use in SE, or in RSE, has been completed.…”
mentioning
confidence: 99%
“…formulations were approved in 2009. A few studies [92] and case reports [93,94] have reported on LCM as an add-on treatment for SE and RSE.…”
Section: Lacosamidementioning
confidence: 99%